The importance of childhood social capitals in the future well-being of children - Hosoda, Chihiro; YunFeng, Zhang; Watanabe, Junji; Maruya, Kazushi; Tabuchi, Rokuro; Hosokawa, Kenchi; Matsuhashi, Takuto (Frontiers in Psychology, 2024)
Introduction Elucidating the enduring effects of childhood social capital is vital for shaping future well-being. Here, we investigate the impact of childhood social capital (SC) and parental engagement on adult psychological well-being and cognitive performance. Methods Utilizing a cohort of 292 Japanese university students, we assessed the influences of SC and parental time during childhood on adult outcomes. Participants retrospectively reported their early childhood experiences, focusing on social interactions and parental involvement. Results Our findings reveal a significant positive correlation between childhood SC and adult subjective well-being, particularly in its positive dimensions. Additionally, maternal involvement during childhood is associated with cognitive abilities in adulthood, as measured by Raven’s Advanced Progressive Matrices. Hierarchical multiple linear regression analysis highlights the substantial impact of childhood SC on adult well-being, elucidating the intricate interplay between social and parental contributions to developmental trajectories. Discussion These results highlight the crucial roles of both parental and non-parental figures in fostering social, emotional, and cognitive development from childhood to adulthood, underscoring the importance of nurturing supportive relationships throughout early life to promote positive developmental outcomes.